A COMPARATIVE STUDY: GENETIC STRUCTURALISM ON JANE EYRE AND THE GREAT GATSBY - Dewi Christa Kobis (BASIS (Bahasa dan Sastra Inggris), 2019)
This study is comparative study which compares Jane Eyre and the Great Gatsby by using Genetic Structuralism. These two novels were written and published from different period. Different period commonly produces different culture, tradition, habit, work, creation, effort, and even different masterpiece. Most people claim that as the time goes by, the old ones will be replaced by the youths, and everything which had been done in the past, might not be done anymore in the present or even in the future. In fact, it is necessary to dig more about the history itself to know how the people at particular period live and how they contribute a society. This study is compiled as a research to study about the characteristic of the society when the novels has been published and the period when the author of the literary works lived while mainly discussed about how different periods create different kind of stories. It also mainly focuses to take a glance on how society impacts the authors’ thought and perception to create such literary works.